Innate immune stimulation prevents the development of anxiety-like behaviors in chronically stressed mice. (1st April 2022) - Shi, Ruiting; Liu, Huijun; Tan, Pingping; Hu, Zhichao; Ma, Yaoying; Ye, Minxiu; Gu, Yue; Wang, Yue; Ye, Ting; Gu, Yiming; Lu, Xu; Huang, Chao
Abstract: Anxiety is a common psychological disease which can induce severe social burdens. Searching methods that prevent the onset of anxiety is of great significance for ameliorating the social and individual problems induced by this type of disease. In this study, we investigated how innate immune pre-stimulation influences the anxiety-like behaviors in chronically stressed mice. Our results showed that a single injection of an innate immune stimulant lipopolysaccharide (LPS) at the dose of 50, 100, and 500 μg/kg 1 day before stress exposure prevented chronic social defeat stress (CSDS)-induced anxiety-like behaviors in mice. A single injection of LPS (100 μg/kg) 5 days before stress exposure produced similar preventive effects on CSDS-induced anxiety-like behaviors, while similar effects were not observed at the condition of 10-days interval between LPS injection and stress exposure. A second LPS injection 10 days after the first LPS injection or a 4 × LPS injection 10 days before stress exposure also prevented CSDS-induced anxiety-like behaviors. Moreover, a single injection of LPS (100 μg/kg) 1 day before stress exposure prevented the production of pro-inflammatory cytokines in the hippocampus and prefrontal cortex of CSDS mice. Suppression of innate immune stimulation by minocycline pretreatment simultaneously abrogated the preventive effect of LPS pre-injection (100 μg/kg) on CSDS-induced anxiety-like behaviors and pro-inflammatory cytokine production in the brain. Our results demonstrated that the pre-stimulation of the innate immune system can prevent the development of anxiety-like behaviors and the progression of the neuroinflammatory responses in the brain in chronically stressed mice. This article is part of the special Issue on 'Stress, Addiction and Plasticity'. Highlights: A single LPS pretreatment prevents CSDS-induced anxiety-like behaviors in mice. 10-days interval abolishes the preventive effect of LPS on anxiety in mice. A second LPS injection still produces preventive effect on anxiety in mice. Repeated LPS injection 10 days prior to stress exposure prevents anxiety onset. Immune inhibition abrogates the preventive effect of LPS on anxiety in mice.